Ablation on polymethylmethacrylate by argon fluoride excimer laser - Zarzali Shah, Aishah; Bidin, Noriah; Mat Daud, Yaacob (Faculty of Science, University Teknologi Malaysia, 2007)
Laser ablation with pulsed uv laser such as excimer laser enables fine micromachining of a variety of optical materials, including organic material. Polymer (organic material) is always been the subject of interest in laser ablation research field. The aim of the research is to analyze the ablation effect on the organic material. Uv light from arf excimer laser was utilized as a source of ablation. The fundamental wavelength of uv light is 193 nm with pulse duration of 12 ns. Pmma was employed as polymer specimen. The target was exposed at variable time of exposure in the range of 5 s to 50 s. The exposed material was analysed using atr-ftir spectrometer. The results obtained showed that the chemical bonding of pmma have been weakened due to the photochemical mechanism. Consequently, this results increases the refractive index of pmma. However, at longer exposure or large number of exposure the physical changes become unstable